Divergent evolution of NLR genes in the genus Glycine: impacts of annuals and perennials’ life history strategies - Sultan, Abu Bakar; Nawaz, Humera; Saleem, Fozia; Nawaz, Sehar; Danial, Muhammad; Iftikhar, Romana; Maqsood, Umer; Areej, Amna; Shakoor, Sidra; Aljarba, Nada H.; Maqbool, Rizwan; Rizwan, Muhammad; et al. (Frontiers in Plant Science, 2024)
Within the family Fabaceae, the genus Glycine is composed of two subgenera annuals (2n=40) and perennials. This life strategy transition may have differentially affected the evolution of various gene families. Its cultivated species G. max has high level of susceptibility to major pathogens including viruses, bacteria and fungi. Understanding nucleotide-binding domain leucine-rich repeat (NLR) genes evolution in soybean is of paramount importance due to their central role in plant immunity and their potential in improving disease resistance in soybean cultivars. In this study, we investigated the significance of this annual-perennial transition on the macroevolution of NLR genes in the genus Glycine. Our results reveal a remarkable distinction between annual species such as Glycine max and Glycine soja, which exhibit an expanded NLRome compared to perennial species (G. cyrtoloba, G. stenophita, G. dolichocarpa, G. falcata, G. syndetika, G. latifolia and G. tomentella). Our evolutionary timescale analysis pinpoints recent accelerated gene duplication events for this expansion, which occurred between 0.1 and 0.5 million years ago, driven predominantly by lineage-specific and terminal duplications. In contrast, perennials initially experienced significant contraction during the diploidisation phase following the Glycine-specific whole-genome duplication event ( 10 million years ago). Despite the reduction in the NLRome, perennial lineages exhibit a unique and highly diversified repertoire of NLR genes with limited interspecies synteny. The investigation of gene gain and loss ratios revealed that this diversification resulted from the birth of novel genes following individual speciation events. Among perennials, G. latifolia, a well-known resistance resource, has the highest ratio of these novel genes in the tertiary gene pool. Our study suggests evolutionary mechanisms, including recombination and transposition, as potential drivers for the emergence of these novel genes. This study also provides evidence for the unbalanced expansion of the NLRome in the Dt subgenome compared with the At subgenome in the young allopolyploid G. dolichocarpa. To the best of our knowledge, this is the first study to investigate the effect of annuality and perenniality life transition on the evolution of NLR genes in the genus Glycine to identify its genomics resources for improving the resistance of soybean crop with global importance on the economy and food security.